Faith in Governance: The Institutional and Legal Frame for the Management of Religion in Singapore - TAN, Eugene K. B. (Institutional Knowledge at Singapore Management University, 2005)
Consider the paradox: Singapore is a secular, multiracial country, yet religion is envisaged to have a role in nation building. Religion exerts a tremendous pull on Singaporeans of various faiths. Given the global phenomenon of religious resurgence, Singapore is buffeted by transnational associational pulls that are more than just emotive and arational. Can a strong religious identity co-exist with a strong Singaporean identity? The paper examines the institutional and legal framework for secularism and the management of religion in Singapore within the governing ethos of multiracialism (which includes multireligiosity). The plethora of institutions overseeing various faiths nestles with a coercive, pre-emptive legislative regime in forestalling any religious extremism and inter-faith conflicts. Yet the fear of vulnerability given the geopolitical sensitivities against the backdrop of the post-September 11th “war against terror” ensure that the scrutiny, surveillance, and sensitivity would be hallmarks of the state’s tightrope walk between secularism and wielding control and influence over religion and its expression for the purposes of state- and nation-building. The policy impulses behind the state’s co-option of religion to reinforce the teaching of moral values, to sustain economic vitality, and to urge the practice of one’s religion in keeping with the secular and multiracial mores of Singaporean society will be examined.